Stimulation Group as an Effort to Increase the Stimulation of Growth and Development of Toddlers in Baratan Jember: Stimulation Group Sebagai Upaya Meningkatkan Stimulasi Tumbuh Kembang Balita di Baratan Jember - Septiyono, Eka Afdi; Merina, Nuning Dwi; Yolanda, Yoga (DEDIKASI SAINTEK Jurnal Pengabdian Masyarakat, 2022)
Infants and children also need sufficient stimulation in quantity and quality from the beginning for their psychosocial mental development. Children who get a lot of stimulation will develop faster than children who get less or even no stimulation. Delays in child development can also be caused by the child's lack of stimulation, caregivers, and parents. Partner problems at this time are health problems. This problem arises because no social institutions have been formed or helped prevent delays in the growth and development of toddlers and the low participation of the community. This low coverage impacts health problems that result in toddlers not fulfilling their growth and development tasks. After discussions with partners and the proposing team, a solution was found to overcome these problems: the stimulation of growth and development through women's empowerment formed through a stimulation group. The counseling results showed that partners' knowledge about growth and development stimulation was in a good category (86%). The training results showed that partners' knowledge about KPSP was in a good category (82%). Stimulation of growth and development should be carried out continuously and appropriately so that it can improve children's abilities in terms of language, social, gross and fine motor skills.